Determinan yang Berpengaruh pada Minat Investasi di Pasar Modal - Sita Dewi, Luh Putu; Gayatri, Gayatri (E-Jurnal Akuntansi; Vol 31 No 5 (2021)DO - 10.24843/EJA.2021.v31.i05.p02, 2021)
Investing in the capital market is an alternative for people who want to invest their excess funds as well as being able to drive the economy in a country. This study aims to obtain empirical evidence regarding the determinants that influence investment interest in the capital market. Determination of the sample in this study using purposive sampling method with a sample of 105 students who have taken the capital market theory course and already have an account of effects. The data analysis technique used is multiple linear regression analysis. The results of the study indicate that investment understanding, motivation, and the bandwagon effect have a positive effect on investment interest in the capital market. This means that the higher the understanding of investment, motivation, and the bandwagon effect phenomenon that occurs, the higher the interest in investing in the capital market. Keywords: Investing Interest; Investment Understanding; Motivation; Bandwagon Effect.